The Andean South at the end of the 18th century: cacique or corregidor - O'Phelan Godoy, Scarlett (1978)
It was after the rebellion of Túpac Amaru (1780), that important demands were finally achieved for which the peasant population had been fighting insistently since the second half of the 18th century. The dissolution of the corregidores and consequently the elimination of the repudiated corregidores, together with the abolition of the distribution of merchandise (the main sucker for the peasant labor force), undoubtedly constituted the most outstanding achievements.